2015
DOI: 10.1039/c5ta01730k
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid physical–chemical deposition process at ultra-low temperatures for high-performance perovskite solar cells

Abstract: The quality of a perovskite film will directly determine the performance and stability of the corresponding perovskite solar cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 23 publications
(29 reference statements)
1
44
0
1
Order By: Relevance
“…10 A variety of methods including solution processing, 11,12 vacuum deposition [13][14][15][16] and vapor-assisted solution processing, [17][18][19] HCVD, 20 HPCVD, 21,22 LPVASP 23 etc. have been applied to fabricate perovskite lms.…”
Section: -3mentioning
confidence: 99%
“…10 A variety of methods including solution processing, 11,12 vacuum deposition [13][14][15][16] and vapor-assisted solution processing, [17][18][19] HCVD, 20 HPCVD, 21,22 LPVASP 23 etc. have been applied to fabricate perovskite lms.…”
Section: -3mentioning
confidence: 99%
“…40 A similar work reported the fabrication of CH 3 NH 3 PbI 3 perovskite films under working pressure of 1 Torr with reaction time of 1 h and temperature of 120…”
mentioning
confidence: 99%
“…Reports of devices that were fabricated by utilizing this technique approached PCEs of g = 12.2% for a small device area. Peng et al [180] demonstrated that the MAPI conversion carried out in a tube furnace with very precise temperature control can lead to enhanced stability that retained above 80% of the original PCE after 30 days of storage in a glovebox. [178] Liu et al [179] refrained from the use of a carrier gas but included NH 4 Cl for the crystal growth assistance that chlorine addition can provide.…”
Section: Chemical Vapor Deposition Processesmentioning
confidence: 99%